Constituição do ensino superior em Bento Gonçalves/RS : Fundação Educacional da Região dos Vinhedos (1955-1972) - Ferreira, Jésica Storchi (My University, 2018)
This dissertation investigated the process of constitution of High Education in the municipality of Bento Gonçalves/RS, in the decades of 1950 to 1970, directly observing the creation of Fundação Educacional da Região dos Vinhedos. This study was developed within the line of research History and Philiosophy of Education, of the Program of Post-Graduation in Education of Universidade de Caxias do Sul. The temporal cut of the study is the year of 1955, when the first articulation of teachers of Model Office Félix Faccenda occurred, with the aim of installing a high education course in this municipality up to 1972, when Fundação Educacional da Região dos Vinhedos (Educational Foundation of Wineries’ Region) (FERVI) was founded. This work was based on the Cultural History approach, related to History of Education, supported by authors as Chartier (1991, 2002), Certeau (2002, 2012), Burke (2008, 2011), among others. The methodology used was document analysis and oral history. To make Document Analysis effective, the study was supported on Le Goff (1996), Alberti (2004), Bacellar (2010), and on Oral History, on Le Goff (1996), Halbwachs (2006), Meihy (2005). Regarding categories for analysis for the research, the authors selected to base it on are Gomes and Hansen (2016) to understand culture mediators, Sirinelli (2003), for comprehension of sociability networks, and Foucault (2017) to establish existing power relationships in the process of constitution of High Education in Bento Gonçalves. The narrative referred made possible the comprehension of the historic context of the municipality in the period of the temporal cut mentioned, as well as the emergence and articulations made to obtain the first high education course. Besides, it was possible to understand the process of consolidation of high education, with the emergence of the High Education Institution, FERVI, was made effective with the involvement of Bento Gonçalves community. The constitution of High Education was possible to occur due to the initiative an articulation of two groups of culture mediators, (a) educational leaders, (b) political leaders, and also, due to the links established in its social networks. Power relations permeated all the process of constitution of High Education in the municipality. The peak of the process of constitution was the installation of the University “Campus”, Bento Gonçalves, as an extension of Universidade de Caxias do Sul (UCS) and the course of Economic Sciences, located at the School of Viticulture and Oenology (Escola de Viticultura e Enologia) (EVE) of the municipality. The act of its installation represented an alliance among UCS, EVE, and culture mediators of the municipality. From that moment on, other courses were installed, as Modern Languages and Sciences, in 1970, concerned with meeting the demand by the female public and teacher education. The graduation of the first group of economists, from the first course, in 1971, contributed for the recognition of the course by the Ministry of Education and Culture, and in 1972, FERVI was created, as a keeper for high education courses, and it became an Isolated High Education Institution. It was constituted by the efforts of merchants, public servants, political leaders, educational and especially the business community, that supported and participated in the project of the cultural mediators.
Esta dissertação investigou o processo de constituição do Ensino Superior no município de Bento Gonçalves/RS, com delimitação temporal entre os anos de 1955 e 1972, atentando para a criação da Fundação Educacional da Região dos Vinhedos. Este estudo foi desenvolvido na linha de pesquisa em História e Filosofia da Educação, do Programa de Pós-Graduação em Educação da Universidade de Caxias do Sul. O recorte temporal do estudo é de 1955, ano em que aconteceu a primeira articulação dos professores do Escritório Modelo Félix Faccenda, com o objetivo da instalação de um curso superior no município, até 1972, quando ocorreu a criação da Fundação Educacional da Região dos Vinhedos (FERVI). Este trabalho fundamentou-se na perspectiva da História Cultural relacionada com a História da Educação, baseando-se assim, em estudiosos como Chartier (1991, 2002), Certeau (2002, 2012), Burke (2008, 2011), dentre outros. A metodologia utilizada foi a análise documental e a história oral. Para efetivar a Análise Documental, o estudo apoiou-se em Le Goff (1996), Alberti (2004), Bacellar (2010), e na História Oral, em Le Goff (1996), Halbwachs (2006), Meihy (2005). Quanto às categorias de análise da pesquisa, a dissertação baseou-se em Gomes e Hansen (2016) para entender mediadores culturais, Sirinelli (2003) na compreensão das redes de sociabilidade e em Foucault (2017) para estabelecer as relações de poder existentes no processo de constituição do Ensino Superior de Bento Gonçalves. A referente dissertação possibilitou a compreensão do contexto histórico do município no período do recorte temporal, bem como a emergência e as articulações realizadas para a obtenção do 1º curso superior. Além disso, foi possível entender que o processo de consolidação do Ensino Superior com o surgimento da Instituição FERVI, efetivou-se com o envolvimento da comunidade bento-gonçalvense. A constituição do Ensino Superior só foi possível pela iniciativa e articulação de dois grupos de mediadores culturais: lideranças educacionais e lideranças políticas, e também pelos vínculos estabelecidos em suas redes de sociabilidade. As relações de poder permearam todo o processo de constituição do Ensino Superior no município. O ápice desse processo foi a instalação do “Campus” Universitário de Bento Gonçalves, como extensão da Universidade de Caxias do Sul (UCS) e o curso de Ciências Econômicas, sediados na Escola de Viticultura e Enologia (EVE) do município. O ato de instalação representou uma aliança da UCS, da EVE e dos mediadores culturais do município. A partir daí, ampliaram-se os cursos, instalando-se Letras e Ciências, em 1970, com a preocupação de atender à demanda de formação de professores e ao público feminino. A formatura da primeira turma de economistas do primeiro curso, em 1971, contribuiu para que houvesse o reconhecimento do curso pelo Ministério de Educação e Cultura e, em 1972, criou-se a FERVI, como mantenedora dos cursos superiores, tornando-se uma Instituição de Ensino Superior Isolada. Ela foi constituída pelo esforço de comerciantes, servidores públicos, lideranças políticas, educacionais e principalmente da comunidade empresarial, que apoiou e participou do projeto dos mediadores culturais.
Keywords: Ensino superior - História - Bento Gonçalves (RS); Fundação Educacional da Região dos Vinhedos; Higher Education - History - Bento Gonçalves (Brazil)